Bibliometric analysis of sports tourism and social media (Agora for Physical Education and Sport, 2021)
Sports tourism, although being a relatively recent type of tourism, has grown significantly in all its aspects. The digital evolution itself is in a constant growth, as well as the generated impact of social media. Considering the increase in both sectors, an examination of how scientific research has adapted to these new realities is required. Hence, the aim of this study is to show the current state of scientific research regarding the field of sports tourism and social media. For this purpose, a search in the databases of WoS and Scopus was performed. Quantitative methods were applied for a co-word analysis, using the SciMat tool.  The results conclude, that the main motor themes of the three analysed periods, "sport", "human" and "sport-event", are closely related to "social-media" and "social-network".
Keywords: bibliometric analysis; sports tourism; sport events; social media; science mapping